Silverfish Lepisma saccharina Linnaeus (Insecta: Zygentoma: Lepismatidae) - Eleanor F. Phillips; Jennifer Lynn Gillett-Kaufman (EDIS)
Silverfish is a common name used to refer to many species in the order Zygentoma. The Entomological Society of America designates the term silverfish as the official common name to only one species, however: Lepisma saccharina Linnaeus. Lepisma saccharina is a pest in urban settings. It is a voracious feeder on materials high in starches, glue, and cellulose such as paper. Lepisma saccharina is a common pest in libraries and museums where paper books and labels are abundant. It can also be found outdoors under rocks, leaf litter, in caves, and in ant nests. Includes: Introduction - Distribution - Description - Life Stages and Biology - Hosts - Economic Importance - Survey and Detection - Management - Selected References. https://edis.ifas.ufl.edu/in1211